PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN, GAYA KEPEMIMPINAN DAN KOMITMEN ORGANISASI TERHADAP KINERJA APARATUR PEMERINTAH DI LINGKUNGAN DINAS PENDIDIKAN KABUPATEN PATI - Fikri, Tazkiyatul; Istanti, Sri Layla Wahyu (JAB (Jurnal Akuntansi & Bisnis), 2016)
ABSTRACTPerformance in Government Performance Accountability (AKIP) as stipulated in Presidential Decree No. 7 The year 1999 was a picture of the level of achievement of the implementation of activities or programs or discretion in accordance targets and goals set forth in realizing the goals, objectives, vision and mission of the organization. Performance Government officials in the Environment Department of Education is influenced by several factors, both related to labor itself as well as those related to the environment either governmental or formal organization in this case non-formal schools and organizations such as early childhood education and courses. Variables money used in this study is budgeting participation, leadership style and organizational commitment. The population of the whole entire Structural Echelon III and IV in the Environmental Education Office of Pati number of 41 respondents. From the test results showed that seluru statement instrument valid and reliable. Hypothesis test results showed that budget participation, leadership style and organizational commitment significant positive effect on the environmental performance of the government apparatus in Pati District Education Office.Keywords : budgeting participation, leadership styles, organizational commitment, the performance of the government apparatus